2008
DOI: 10.4315/0362-028x-71.7.1465
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Water-Soluble Muscadine Seed Extracts on Escherichia coli O157:H7

Abstract: Water-soluble extracts were prepared from purple (cultivar Ison) and bronze (cultivar Carlos) muscadine seeds with or without heating. The Ison extracts had strong antimicrobial activity against a cocktail of three strains of Escherichia coli O157: H7. This extract had higher acidity (pH 3.39 to 3.43), total phenolics (2.21 to 3.49 mg/ml), tartaric acid (5.6 to 10.7 mg/ml), tannic acid (5.7 to 8.1 mg/ml), and gallic acid (0.33 to 0.59 mg/ml) than did the Carlos extracts. Heat treatment on both extracts increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Initial plating studies using agitated cell suspensions in 0.85% saline produced large (,6-log) reductions in cell viability within 10 min with 1,250 mg ml 21 GSE (25). These results are consistent with those reported by other researchers for L. monocytogenes and other pathogens (10,11,20). However, after reviewing the literature, we hypothesized that residual activity of GSE might contribute to an overestimation of the antimicrobial effects of GSE.…”
Section: Mic Of Gsesupporting
confidence: 92%
See 1 more Smart Citation
“…Initial plating studies using agitated cell suspensions in 0.85% saline produced large (,6-log) reductions in cell viability within 10 min with 1,250 mg ml 21 GSE (25). These results are consistent with those reported by other researchers for L. monocytogenes and other pathogens (10,11,20). However, after reviewing the literature, we hypothesized that residual activity of GSE might contribute to an overestimation of the antimicrobial effects of GSE.…”
Section: Mic Of Gsesupporting
confidence: 92%
“…These results indicate that the commercial GSE we evaluated contains acidic compounds that may lower the pH of the test system in a dose-related fashion. Tartaric acid is the major organic acid present in GSE, and such organic acids have been suggested to play a large role in GSE activities against E. coli O157:H7 and E. sakazakii (10,11). However, Rhodes et al (20) found that adjusting the pH of grape seed polymeric phenolics from 3.5 to 7.0 did not affect the antimicrobial activity of these phenolics against L. monocytogenes, and Mayer et al (16) fractionated GSE via chromatography and found the highest antimicrobial activities in fractions containing proanthocyanidins and their gallate esters.…”
Section: Resultsmentioning
confidence: 99%
“…Thiosulfinates are prepared from garlic by mild procedures. They have strong antimicrobial activities against Gram-negative bacteria (Kim et al, 2008;Naidu, 2000a;Yoshida et al, 1999). Glucosinolates are present in broccoli, brussels sprouts, cabbage, and mustard powder and cause the pungent flavor of mustard and horseradish.…”
Section: Chemical Components Present In Eosmentioning
confidence: 99%
“…Generally, phenolic compounds of EOs such as citrus oils extracted from lemon, olive oil (oleuropein) and tea-tree oil (terpenoids), orange and bergamot have broader antimicrobial effects and are not categorized as spices. Meanwhile, there are increasing reports of nonphenolic compounds of oils, which are effective against both Gram-positive and Gram-negative groups, from oregano, clove, cinnamon, citral, garlic, coriander, rosemary, parsley, lemongrass, purple (cultivar Ison) and bronze (cultivar Carlos) muscadine seeds and sage (Angioni et al, 2004;Daferera et al, 2000;Davidson & Naidu, 2000;El-Seedi et al, 2008;Fisher & Phillips, 2006;Gutierrez et al, 2008a;Holley & Patel, 2005;Kim, Marshall, Cornell, Preston, & Wei, 1995;Kim et al, 2008;Lopes-Lutz et al, 2008;Naidu, 2000b;Nejad Ebrahimi, Hadian, Mirjalili, Sonboli, & Yousefzadi, 2008;Mandalari et al, 2007;Nguefack et al, 2007;Oussalah et al, 2004;Santos & Rao, 2001;Skocibusic et al, 2006;Yoshida et al, 1999).…”
Section: Chemical Components Present In Eosmentioning
confidence: 99%
See 1 more Smart Citation